GENDER STRUGGLE IN DEBORAH ELLIS’ PARVANA MUD CITY - Zaindy Roby Hilaldo; Eko Suwargono; L. Dyah Purwita Wardani (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2019)
This article dicusses the gender struggle of Shauzia in Mud City by Ellis. The struggle implies the gender condition and critical point of view of the author based on the theory of representation and gender oppression. The representation theory based on Stuart Hall helps to uncover the dominating cultural codes which oppress Shauzia as a person while the gender theory contributes to analyze the layer of dominationin the level of individual, interactional and institutional. This study results in several findings as:the cultural codes represented in the novel are giving benefit the man by the power of military and powerful patriarchy where Shauzia finds hard to go out from camp and work as woman. Furthermore, gender theory plays on scrutinizing the idea as individual woman lacks of rights, and influence her interactional competence as well to stay inside the compound. The institutional system determines her exixtence only to accept what the compound has given to her and not more. Thus she is rejected when she wants to go to France. Ellis poses her self to tell the reader that the value of women in Afganistan at war is unworthy compare to what happens in Europe.